2012
DOI: 10.1111/1742-6723.12019
|View full text |Cite
|
Sign up to set email alerts
|

Triggers for head computed tomography following paediatric head injury: Comparison of physicians' reported practice and clinical decision rules

Abstract: High-quality, published CDRs exist for head CT use after paediatric head injury. Physician-reported CT triggers differ from CDR-recommended triggers. The major published head injury CDRs should be prospectively validated in the Australasian setting before incorporating them into local practice and CPGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
0
28
0
2
Order By: Relevance
“…A further limitation is that CT scans were not reviewed centrally; rather CT reports were used to assess ICI. Finally, this study reflects practice at tertiary Australian and New Zealand centres, where imaging rates are generally lower than in North America6 7 11 24 and no specific rule predominates 25. The developers of NEXUS presumed that patients in the derivation study perceived by clinicians to be at high risk (independent of the NEXUS criteria per se) would be imaged by treating clinicians anyway.…”
Section: Discussionmentioning
confidence: 94%
“…A further limitation is that CT scans were not reviewed centrally; rather CT reports were used to assess ICI. Finally, this study reflects practice at tertiary Australian and New Zealand centres, where imaging rates are generally lower than in North America6 7 11 24 and no specific rule predominates 25. The developers of NEXUS presumed that patients in the derivation study perceived by clinicians to be at high risk (independent of the NEXUS criteria per se) would be imaged by treating clinicians anyway.…”
Section: Discussionmentioning
confidence: 94%
“…A recent survey of Australian paediatricians and emergency physicians examined factors contributing to the ordering of CTBs . It was found that Australian practitioners were not using all triggers suggested by existing CDRs when deciding whether or not to perform a CTB.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been partly due to the various specialties involved in the care of these children, the large amount of criteria in the guidelines and the fact that they could be interpreted in a number of ways. In addition, objective clinical findings have been shown to be more commonly used as the criteria for performing a CT scan than historical factors . Consequently, there was a large variation in the care of children with MTHI in the Netherlands.…”
Section: Adherence To Major Criteria To Perform a Ct Scan In Childrenmentioning
confidence: 99%